Perforated gastroduodenal ulcer. Laparoscopic treatment - Morelli Brum, Raúl; Praderi Gambardella, Luis A; Veirano, Gustavo; Bermúdez, Jorge (Cirugía del Uruguay, 1996)
The authors present two cases of perforated gastroduodenal ulcus which were treated by means of laparoscopy. They insist on the convenience of treating peritonitis by means of laparoscopy if the patient is stable from the hemodynamic points of view. Real benefits consist of mínimum parietal sequels, pain decrease and earlier return to work